A new automated approach to determine monosodium glutamate in dehydrated broths by using the flow-batch methodology - Acebal, Carolina Cecilia (2010)
The advantages of the flow-batch methodology were exploited to implement a simple system with nephelometric detection for the determination of monosodium glutamate (MSG) in food samples. The method is based on the inhibitory effect of the MSG over the crystallization of l-lysine in an isopropanol/acetone mixture. The calibration curve was prepared on-line. The method was linear over the range of 2.8 × 10-3 to 1.1 × 10-2 g L-1 and a detection limit of 9.7 × 10-5 g L-1 was achieved. It was successfully applied to determine the MSG concentration in food samples, without a previous treatment. A recovery study was carried out on real samples and the percentages were between 98 and 106%.